Pembelajaran Di Abad Ke-21 Dengan Model Project Based Learning (PJBL) - Handiani, Mezeza Putri (Universitas Dehasen Bengkulu, 2025)
This research is a review of 15 studies that discuss the application of the Project Based Learning (PjBL) model in Indonesian language learning, especially in developing writing skills and understanding material. The aim is to determine the effectiveness of PjBL in various learning contexts, including learning explanatory texts, news texts, anecdotal texts, descriptive texts, and others. Overall, the research results show that the implementation of PjBL has succeeded in increasing students' active involvement, creativity, independence and writing skills. However, challenges such as the lack of creativity of students in some groups and the implementation of the initial stages of learning are still important notes.